Development of a novel buckling-restrained damper with additional friction energy dissipation: Component tests and structural verification. (1st January 2023) - Lu, Yujie; Liu, Ye; Wang, Yuhao; Liu, Jingjing; Huang, Xiaogang
Highlights: Proposal of a novel buckling-restrained damper with friction energy dissipation. Low-cycle fatigue tests on nine BFD specimens considering four parameters. Numerical analyses on the seismic effectiveness of the BFD in a SDOF system. Abstract: Aiming at solving the issue of the conventional buckling-restrained brace, i.e., the fixed yield strength and residual deformation, a novel buckling-restrained damper with additional friction energy dissipation (BFD) was proposed and tested in the present study. By fabricating an inner core with a small yield segment (SYS) and a large yield segment (LYS) connected in series and setting a friction device in parallel with the SYS, the dual stiffness and stable energy dissipation capacity of the BFD were achieved. Low-cycle fatigue tests were conducted on nine BFD specimens to investigate the influences of the length of the LYS, the length of the slotted holes, the bolt torque and the loading protocol on the hysteretic behavior of the BFD. The experimental results demonstrated that the strength of the BFD increased with the maximum strain of the LYS, whereas the low-cycle fatigue life of the BFD was negatively affected by the maximum strain of the LYS. The friction energy dissipation device could enhance the energy dissipation capability of the BFD throughout the working process. Moreover, the results from the numerical case study determined that the BFD could effectively control the displacement response of the SDOF system under different earthquake magnitudes.